Over dose effect of Oxytetracycline in some biochemical and hematological parameters in rats - Nashat Mustafa (College of Education for Pure Sciences, 2005)
Oxytetracycline is the most important used antibiotic in the field of treatment of infectious animal diseases, therefore we perform this research to study the effects of this important antibiotic on some biochemical and hematological parameters , Twenty eight adult male albino rats were used, which divided into four groups (7 rats for each group) : control group: was injected with distilled water , group 2 was given normal dose (lOOmg/kg of B.W) group 3 was given high dose (500mg/kg of B.W) group 4 was given very high dose (lOOOmg/kg of B.W), Oxytetracycline was injected daily for three days, and in the fourth day hemoglobin concentration and PCV% were estimated , Serum was separated and S.Glucose , S. Cholesterol , and S. Urea were determined using Kits (Randox Co. England made) . Results show insignificant effects of normal dose except a decrease in S,Cholesterol . The high dose produce a significant increase in S.Glucose and decrease in S. Cholesterol without any effect on other parameters .Injection of very high dose of Oxytetracycline cause a decrease in S. Cholesterol, Hb and PCV , with an increase in S. Glucose and S. Urea levels , we conclude that Oxytetracycline has obvious effect on both biochemical and hematological values, and this effect is more clear by increasing the dose of Oxytetracycline . الخلاصة